The Effectiveness of TED-ED Videos as Audiovisual Input in Listening Activities - Divya Ayu Damayanti; Sumarniningsih Sumarniningsih (Universitas Pahlawan Tuanku Tambusai, 2022)
Technology, Entertainment, Design, and Education (TED-Ed) is a free online website which provides several authentic video materials covering educational topics and current issues for public consumers, particularly EFL teachers and students. Listening skill is an important part in second or foreign language learning because the students acquire new spoken language and target vocabularies used in daily communications. Hence, TED-ED can be applied as authentic listening materials in EFL classrooms to enhance student’s listening skill. This present study aims to find whether there is a significant difference in listening skills between students who were taught by TED-ED videos and those who were taught by other kinds of videos. The population of the study was 60 eleventh grade students from one of the private schools in Surabaya. This quantitative research collected the data from a listening comprehension test and a questionnaire. The researcher used an independent sample T-test to analyse the data in IBM SPSS 25 application. The result found that t-test score was 2.176 higher than critical value for 58 degrees of freedom (df), the mean of the experimental group (TED-ED) was 71.30 and the control group (other kinds of videos) was 66.20. Therefore, it proved that there was a significantly difference in listening skills between students who were taught by TED-ED videos and those who were taught by other kinds of videos. This study also got positive perception toward TED-ED utilized in listening activities from students.